Vibrational spectra of light and heavy water with application to neutron cross section calculations - Marquez Damian, Jose Ignacio (2013)
The design of nuclear reactors and neutron moderators require a good representation of the interaction of low energy (E < 1 eV) neutrons with hydrogen and deuterium containing materials. These models are based on the dynamics of the material, represented by its vibrational spectrum. In this paper, we show calculations of the frequency spectrum for light and heavy water at room temperature using two flexible point charge potentials: SPC-MPG and TIP4P/2005f. The results are compared with experimental measurements, with emphasis on inelastic neutron scattering data. Finally, the resulting spectra are applied to calculation of neutron scattering cross sections for these materials, which were found to be a significant improvement over library data.